Bionanocomposites for Natural Food Packing - Cherian, Bibin Mathew [UNESP]; De Olyveira, Gabriel Molina; Costa, Ligia Maria Manzine; Leão, Alcides Lopes [UNESP]; De Morais Chaves, Marcia Rodrigues; De Souza, Sivoney Ferreira; Narine, Suresh (Wiley, 2013)
Food packaging is essential for preserving food during the period between production and ultimate consumption. Considering the current problems associated with food production, such as global warming, rising demand for food, occasioned by increased population, reduced arable land, competition between food and fuel production, it is necessary to adopt measures aimed at reducing food losses. Nanotechnology applied to packaging emerges as an effective alternative to minimize losses and increase food security Nanomaterials confer greater chemical, physical and biological resistance to packaging, and increase food shelf life. Moreover, packaging represents an environmental problem after use since it is produced from petroleum-based polymers, and is nonrenewable and non-biodegradable. It also contributes to the vast amount of waste disposal as well. In this context, the development of packaging based on renewable and biodegradable materials such as starch and cellulose, is critical to the sustainability of the food system. Due to the technological problems of the matrices, nanomaterials play a fundamental role in obtaining biodegradable packaging with efficiency similar or superior to traditional packaging. In this chapter we will present an overview of recent scientific studies related to obtaining bionanocomposites for application in food packaging, especially in films, considering its properties and relations between different nanomaterials and matrices. The toxicological aspects of bionanocomposites are also briefly discussed. © 2013 Scrivener Publishing LLC. All rights reserved.
Keywords: Bionanocomposites; Food nanoparticle additives; Food packing; Nanocrystals; Nanofibers; Nanoreinforcements; Polysaccharide films; Surface modification; Toxicology